2020
DOI: 10.1038/s41598-019-57355-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of adjacent segmental fractures when percutaneous vertebroplasty is performed for the treatment of osteoporotic thoracolumbar fractures

Abstract: The study aimed to analyze the radiographic and magnetic resonance imaging (MRI) findings that might predict the risk for adjacent segmental fractures (ASfs) when percutaneous vertebroplasty (PV) is used for the treatment of osteoporotic thoracolumbar fractures (OTFs). A total of 92 OTFs patients who underwent PV between January 2013 and January 2015 were retrospectively reviewed. the visual analog scale (VAS), oswestry-Disability index (oDi) and radiolographic measurements were assessed. The VAS and ODI score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Although the surgeons use analgesics to reduce patients' intraoperative pain, adverse reactions could bring more risks for geriatric patients. How to improve the effectiveness of local anesthesia still remains an issue (11)(12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Although the surgeons use analgesics to reduce patients' intraoperative pain, adverse reactions could bring more risks for geriatric patients. How to improve the effectiveness of local anesthesia still remains an issue (11)(12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Bone cement strengthens the compressed vertebral body to treat OVCFs, and the prognosis of PVP is affected by BMD, bone cement distribution, etc. 1 , 2 , 9 , 10 It was reported that the patients with thoracic and lumbar compressed fractures according to the type of diffusion of bone cement and found that the vertebral body with poor diffusion of bone cement may have unstable spines, leading to postoperative re-compression of the fractured vertebral body and aggravating clinical symptoms. 11 Previous studies have pointed out that preoperative severe kyphotic deformities, solid lump cement distribution patterns, and larger reduction angles are risk factors for the development of recollapse; among these risk factors, the solid lump cement distribution pattern is the most significant.…”
Section: Discussionmentioning
confidence: 99%
“…It was conducted grouping studies on the distribution of bone cement according to whether the bone cement touched the upper and lower endplates and found that when the bone cement touched the upper and lower endplates, the vertebral strength could better recover to maintain the height of the vertebral body and reduce the risk of vertebral recompression. 10 , 11 It has been reported that when there is bone cement distribution around the upper and lower endplates, the rate of vertebral recompression may be lower than that of endplates without bone cement distribution. 15 In a finite element analysis of bone cement distribution, it was found that if only one side of the endplate was surrounded by bone cement, the vertebral stiffness only increased 2 fold, with almost no change in strength.…”
Section: Discussionmentioning
confidence: 99%
“…After the satisfactory correction effect is achieved, the bone cement is injected into the cavity formed by the expansion of the balloon. The bearing capacity of the bone cement after solidification can provide reliable support for the injured vertebrae 9 , 10 , 11 .…”
Section: Discussionmentioning
confidence: 99%